HAFEZ AL-ASSAD AND THE ISSUES BEHIND SYRIA'S PROTRACTED CONFLICT (International Conference on Social and Islamic Studies, 2022)
This paper describes one of the influential figures in the Arab world, namely Hafez al-Assa'd. The method used is descriptive qualitative research, by analyzing, describing the life history (individual life history) of the person being studied and the socio-historical conditions in which the character lived. This paper provides an overview of the figure of al-Assa'd and the issues of conflict in Syria. The results of the study show that Hafez al-Assa'd by joining the military, especially the Syrian air force, smoothed the habit of taking strategic positions in the government, which later made him president of Syria for 30 years. The conflict in Syria is a prolonged conflict that involves many parties, both pro-government and opponents, organizations, interests and the state. Issues that are always heralded by religious conflicts and disharmony between Sunnis and Shiites, are only one of the factors that cause major wars in the country. Many other factors have caused a prolonged war in Syria, among others, caused by economic, political, ideological, defense and "foreign" interests.